Factors associated with utilization of skilled birth attendance among women of reproductive age in North Horr Sub-County, Northern Kenya, 2021 - Qabale Anna Duba; Elvis Omondi Oyugi; Paul Nyongesa; Joseph Obiero Ogutu (Journal of Interventional Epidemiology and Public Health)
Introduction: One of the ways of reducing the maternal mortality ratio (MMR) is through skilled birth attendance. Kenya's Maternal Mortality Ratio (MMR) declined from 362 to 353 deaths per 100,000 live births between 2014 and 2021. However, MMR for Marsabit County has remained high, with 1,127 deaths per 100,000, and only a small proportion of births are conducted by skilled birth attendants. We identified the factors associated with the utilization of skilled birth attendant services in North Horr Sub-County, in arid Northern Kenya. Methods: We conducted a crosssectional study in November–December 2021. A multistage, sampling technique was used to identify women with children aged below 5 years. We interviewed the women using structured questionnaires and performed descriptive statistics. We computed the crude odds ratios (COR) at the bivariate analysis and the adjusted odds ratios (aOR) at the multivariable analysis together with their corresponding 95% confidence intervals (CI), and p-values to identify the factors associated with utilizing skilled birth attendance. We considered factors with p<0.05 at the multivariable level as independently associated with the utilization of skilled birth attendants. Results: We interviewed 294 women. The mean age was 28.5 years (SD±5.9 years), 46% (135/294) were aged 15–27 years, and 42.2% (124/294) had delivered in a health facility. The mean age was 28.5 years (SD±5.9 years), 46% (135/294) were aged 18–27 years and 42.2% (124/294) had delivered in a health facility and 58.5% (172/294) earned less than Ksh 1,000 (USD 8) as monthly income. A total of 284 (96.6%) were married, 50.3% (148/294) were Muslims, and only 9.25% (27/294) had attended at least four Antenatal Care (ANC) visits. In the logistic regression model for determinants of skilled birth attendance services, being Muslims (aOR 3.86; 95% CI: 2.15–6.91; p=0.000), having a monthly income of more than USD 8 (aOR 2.83; 95% CI: 1.28– 6.27; p < 0.05), living near a health facility (aOR 2.39; 95% CI: 1.33 – 4.28, p=0.011), attending four or more ANC visits (aOR 4.18; 95% CI: 1.03 – 17.18; p = 0.045) and being accompanied by husbands (aOR 9.45; 95% CI: 1.84 – 48.34; p =0.007) were independently associated with utilization of skilled birth attendant services. Conclusion: The skilled birth attendant coverage remained sub-optimal below the national coverage. Distance to facilities, religion, level of income, number of ANC visits, and being accompanied by a spouse were associated with seeking skilled birth attendant services. There is a need to address gaps in the utilization of skilled birth attendants in arid areas by establishing mobile clinics and conducting outreaches in hard-to-reach areas to cut down on travel time. Advocacy programs should also strengthen male involvement.